TgATG9 is required for autophagosome biogenesis and maintenance of chronic infection in Toxoplasma gondii - Pariyamon Thaprawat; Zhihai Zhang; Eric C. Rentchler; Fengrong Wang; Shreya Chalasani; Christopher J. Giuliano; Sebastian Lourido; Manlio Di Cristina; Daniel J. Klionsky; Vern B. Carruthers (Autophagy Reports)
Toxoplasma gondii is a ubiquitous protozoan parasite that can reside long-term within hosts as intracellular tissue cysts comprised of chronic stage bradyzoites. To perturb chronic infection requires a better understanding of the cellular processes that mediate parasite persistence. Macroautophagy/autophagy is a catabolic and homeostatic pathway that is required for T. gondii chronic infection, although the molecular details of this process remain poorly understood. A key step in autophagy is the initial formation of the phagophore that sequesters cytoplasmic components and matures into a double-membraned autophagosome for delivery of the cargo to a cell’s digestive organelle for degradative recycling. While T. gondii appears to have a reduced repertoire of autophagy proteins, it possesses a putative phospholipid scramblase, TgATG9. Through structural modeling and complementation assays, we show herein that TgATG9 can partially rescue bulk autophagy in atg9∆ yeast. We demonstrated the importance of TgATG9 for proper autophagosome dynamics at the subcellular level using three-dimensional live cell lattice light sheet microscopy. Conditional knockdown of TgATG9 in T. gondii after bradyzoite differentiation resulted in markedly reduced parasite viability. Together, our findings provide insights into the molecular dynamics of autophagosome biogenesis within an early-branching eukaryote and pinpoint the indispensable role of autophagy in maintaining T. gondii chronic infection.